A Systematic Review of Ethnomathematics Research (2019–2023): Cultural Integration in Mathematics Teaching and Learning - Setiaputra, Felix Indra; Subanti, Sri; Usodo, Budi; Triyanto, Triyanto; Fitriana, Laila; Hendriyanto, Agus (FKIP Universitas Lampung, 2025)
This systematic literature review (SLR) examines ethnomathematics in the period 2019–2023 using the PRISMA protocol. By analyzing the Scopus and ERIC databases, 24 relevant articles were found. Ethnomathematics is an interdisciplinary field that studies the practices, knowledge, and cultural aspects of mathematics in various societies. This SLR aims to provide an overview of the latest research trends, methodologies, and main findings in ethnomathematics. The review process included analysis of titles, abstracts, and full texts, with data extraction related to the year of publication, authors, research objectives, methodology, and main findings. The data obtained were analyzed to identify research patterns and gaps. The results of the study show an increasing interest in exploring cultural mathematical practices and the impact of cultural factors on mathematics learning. Various methodological approaches were used, such as qualitative, quantitative, ethnographic, and cross-cultural comparison studies. Key findings include the integration of ethnomathematics in education, cultural relevance in the curriculum, and the development of culturally responsive pedagogy. The review also highlights the need for further research, especially related to the representation of underrepresented cultures or regions. Overall, this SLR provides a comprehensive review of recent research in ethnomathematics, identifying trends, methodologies, and key findings. The study contributes to the discussion on cultural diversity and inclusivity in mathematics education, serving as a valuable reference for researchers, educators, and policymakers. Keywords: ethnomodeling, ethnomathematics, systematic literature review (SLR).